"From the Initial Steps to the Concept of Online Education" - Teacher Experiences and Development Directions Based on Feedback from Online Education Introduced During the Pandemic - Mónika Rajcsányi-Molnár; Anetta Bacsa-Bán (Debrecen University Press, 2021)
The pandemic situation caused by COVID-19 has challenged the education system, not only in Hungary, but everywhere in the world. The use of information and communication technology in education, including higher education, has transformed students' expectations and, at the same time, redefined the role of the online educator. This is because online teaching and learning is significantly different from teaching-learning in a traditional environment, and educators need to rethink their role in the learning and teaching paradigm. Our higher education institution has developed a new learning-teaching concept based on the experience of distance education introduced as a result of the pandemic situation. The research described in the study and the corresponding developments are shared as good practice for other higher education institutions.